The Alignment of Business Process In Event Organizer And Enterprise Architecture Using TOGAF - Margaretha - Mei Mei; Johanes Fernandes Andry (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2019)
Event organizer is a company which engaged in event organizing, PR, and advertising. A suitable information systems that fit company's business needs are required so the company can adapt themselves in this globalization era. Information systems had an important role in order to support the company’s business process and its performance. An example of applied information systems that have been widely used by companies is enterprise architecture. Currently, enterprise architecture has been used by many enterprises to be able connect between the planning and the technology implementation to the current business in the company. Enterprise Architecture Planning (EAP) is a method in enterprise architecture which can provides alignment between business and information technology by defining company’s needs. Main components of EAP are data architecture, applications, and technology. The framework that will be used to develop EAP on this research is TOGAF ADM with phases starting from preliminary phase, requirements management, architecture vision, business architecture, information systems architectures, technology architecture, opportunities & solutions, and migration planning. A result on this research will be a blueprint of enterprise architecture model that an event organizer can use in supporting its business. The blueprint contains the current used information systems and the ideal information systems planned by the authors.